Dekonstruksi Orientalisme (Telaah atas Pemikiran Leonard Binder) - Muzakki, Akhmad (ULUL ALBAB Jurnal Studi Islam, 2005)
Ortodox Moslems considered orientalism as a conflict between kafir and mukmin which was sharpened by various tendencies. They appraised, Nurcholis said, because there are three prejudice roots of the West to Islam which caused the emerge of negative stigma that are the prejudices on religious, socio-politic and culture understandings. Or, as stated by Hasan Hanafi, orientalism saw "ego" (East) through "the other". West took apart as "ego" which became the subject and considered non-West as "the other" which became the object. As a consequence of its position as the subject examiner, superiority complexity in the European "ego" aroused Because of its position as the examined object the inferiority complexity in "the other" non Europe emerge as well. In contrast to Foucalt, he said that orientalism is a discourse. Islam is also understood by Moslem as a discourse. Basically, orientalism is an effort to articulate an interpretation of Islam. Therefore, according to orientalism Islam is universal and cannot be given a single interpretation. As stated in the deconstruction theory which views that a language does not have an exact, particular, constant meaning, however, it tries to get the contradictory and ironical meaning. Hence, because orientalists understand Islam as a phenomenon, Islam universaly depends on culture in which it is manifested.